The impact of energy on climate and economic stability: Forecast for Serbia - Nemanja Backović; Miomir Jakšić; Bojan Ilić (Journal of Central Banking Theory and Practice, 2024)
In the conditions of modern business environment of energy companies, studies of their impact on environmental protection are becoming increasingly important. The growing concern at the macro level of the resulting climate change due to energy production is justified. The ecological component in the business of energy entities is becoming a priority for the sustainable development of energy, and therefore must be thoroughly examined. The focus of this paper is to determine the impact of energy on climate change through the emission of Greenhouse Gases on the example of the Republic of Serbia. The paper also examines the long-term interdependence between key economic and energy indicators at the national level. The IPAT/Kaya identity was used for research purposes and three alternative scenarios of energy development in Serbia until year 2050 were developed. The obtained results point to different possibilities for the development of energy and its impact on climate. The importance of promoting renewable energy sources for environmental protection and overall economic stability is also pointed out through proposed alternative scenarios. Significant results were obtained for the predicted level of energy intensity for the observed period, suggesting how the development of energy in Serbia could affect economic stability until 2050.
Keywords: C63; Q43; Q47; Q53; 330; Energy; Climate Change; Economic Stability; IPAT/KayaIdentity; Greenhouse Gases